(untitled) (Journal of Bangladesh Academy of Sciences, 2011)
A pot experiment showed that 100 and 200 ppm naphthalene acetic acid (NAA) plant height, number of leaves per plant and number of tillers per plant were found to increase due to 100 ppm NAA only in BRRI dhan-29 (V1) and varied significantly at 60 DAS. Total dry matter (TDM) was found to increase up to harvest due to both the treatments in V1, whereas, in BRRI dhan-50 (V2) also increased at 15 and 30 DAS and the variation was non-significant. There was an increasing tendency in leaf area per plant due to T1 treatment in both the varieties except at 45 DAS in V2. Significant variations were observed at 15 and 30 DAS only in V1. Relative growth rate (RGR) was maximum at early stage of growth and then declined in both the varieties. RGR was significant during 0 to15 and 45 to 60 DAS in case of V1. Net assimilation rate (NAR) was non-significantly affected and found to increase during 15 to 30 DAS following both the treatments in V1, but in V2 due to T2 treatment only. Out of the two concentrations 100 ppm NAA produced better stimulation. DOI: http://dx.doi.org/10.3329/jbas.v35i1.7976 Journal of Bangladesh Academy of Sciences, Vol.35, No.1, 113-120, 2011